Inflammation and immunosurveillance in breast cancer - Mahmoud, Sahar (2011)
Breast carcinomas are often infiltrated by inflammatory cells, particularly macrophages and T-lymphocytes but the significance of these cells remains unclear. Potential roles include an immune response against the tumour, and pro-tumour effects such as the release of angiogenic factors or proteolytic enzymes. Breast cancer is a remarkably heterogeneous disease embracing a wide range of clinical patterns, stages of presentation, biological behaviour,prognostic characteristics and response to different types of treatment.International efforts have been made to improve survival rate by early diagnosis and multiple therapies. However, the limitations of the current therapeutic modalities have led to increasing enthusiasm for defining new prognostic tools and developing highly targeted therapies.